New Report On AMF Colonization in Root Parasite Striga gesnerioides and its Host Lepidagathis hamiltoniana from High Altitude Region of Maharashtra - Kamble, Vishal R.; Agre, Dinesh G. (International Multidisciplinary Research Journal, 2014)
Present paper deals with in-depth analysis of AMF colonization reported in root parasite Striga gesnerioides (Willd) Vatke. Oester, Var gesnerioides and its host Lepidagathis hamiltoniana Wall. ex Nees collected from from Alang, and Madan Forts situated at high altitude region of Maharashtra. Although AM fungal colonization in S. gesnerioides and its host L. cuspidata has been recently reported, this is the new report with reference to host- parasite system of S. gesnerioides - L. hamiltoniana from high altitude region of Maharashtra.